Comments on the Power of Kolmogorov Test - Andrzej Rogowski (Communications - Scientific letters of the University of Zilina, 2013)
This paper presents the results of estimating the power of Kolmogorov test and its modifications for testing hypothesis about an exponential distribution against the alternative hypothesis (population has a Weibull distribution). The power of test was calculated based on a distribution of empirical cumulative distribution function and limiting distribution, as well as computer-simulation methods. Some important properties and limitations were given that are related to power simulation study of goodness-of-fit tests.